Structural features of near equiatomic FeCo-2V semi-hard magnetic alloy prepared by MIM technology - Nedeljković Borivoje; Pavlović Vladimir B.; Obradović Nina; Mitrović Nebojša (Science of Sintering)
The structural properties of a magnetically semi-hard near equiatomic FeCo-2wt%V (FeCoV) alloy produced by Powder Injection Moulding (PIM) (option by fine metal powder - Metal Injection Moulding (MIM) technology) were investigated in this paper. Starting granulate was prepared by mixing FeCoV powder with a low-viscosity binder. After injection, the green samples were first treated with a solvent and then thermally with the same aim of removing the binder. MIM technology was completed by high-temperature sintering for 3.5 hours at temperatures from 1370 to 1460°C in a hydrogen atmosphere, which provides the necessary magnetic and mechanical characteristics. The influence of sintering temperature was investigated concerning the aspects of the processes of structural transformation by the methods of X-ray diffraction (XRD) and scanning electron microscopy (SEM). The appearance of an intense diffraction peak of the α'- FeCo phase (crystal structure type B2) was registered for all investigated samples. Structural parameters particle size Dmax, Feret X, and Feret Y exhibit constant increase with increase of sintering temperature.